(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The first thing the COVID-19 teaches the public is to keep your hands clean and safe. The demand for hand sanitizers has suddenly grown because using these products is one of the strategies to defend against COVID-19. Sanitizers and masks were classified "necessary goods" by the Indian government under the Essential Commodities Act. The government has set the price of a 200ml bottle of hand sanitizer at Rs.100/-. Furthermore, the Indian government set the price of sanitizers at 2ml for no more than Re.1/-.The objectives of the research study are to adapt the five-stage consumer decision making model (Kotler et al. (2009)) for the hand sanitizer product in the COVID-19 scenario and to adapt and define the scale items related to each stage of the consumer decision making process with regard to the hand sanitizer product. The findings indicate that consumers demonstrate regular purchasing behaviour when they are happy with an emergency product (hand sanitizer product in covid-19 scenario). Consumers will prefer to acquire emergency-related products solely from approved stores (like medical outlet).